Association of CD209 and CD209L polymorphisms with tuberculosis infection in a Northeastern Brazilian population. - da Silva, Ronaldo Celerino; Segat, Ludovica; da Cruz, Heidi Lacerda Alves; Schindler, Haiana Charifker; Montenegro, Lilian Maria Lapa; Crovella, Sergio; Guimarães, Rafael Lima (Mol Biol Rep, 2014)
Tuberculosis (TB) caused by Mycobacterium tuberculosis, is major cause of morbidity and mortality worldwide. So far, many candidate genes have been investigated for their possible association with TB. Dendritic cell-specific intercellular adhesion molecule 3 (ICAM-3) grabbing non-integrin (DC-SIGN) and Liver/lymph node-specific intercellular adhesion molecule-grabbing non-integrin (L-SIGN), encoded by CD209 and CD209L genes respectively, are known for binding to M. tuberculosis on human dendritic cells and macrophages. We screened 4 single nucleotide polymorphisms (SNPs) in the promoter region of CD209, namely -939G>A (rs735240), -871A>G (rs735239), -336A>G (rs4804803) and -139G>A (rs2287886) and tandem repeat polymorphisms in exon 4 of CD209 and CD209L genes looking for association with TB in a Northeastern Brazilian population (295 subjects, 131 TB patients and 164 healthy controls). The -139G>A and -939G>A SNPs were associated with susceptibility to TB, and in particular with pulmonary and extra-pulmonary forms respectively. The -871A>G and -336A>G SNPs were associated, the first with protection to both pulmonary and extra-pulmonary TB, the latter only with the pulmonary form. An association between GGAG haplotype and protection to TB infection was also found. Also tandem repeat polymorphism in CD209L exon 4 was associated with TB infection. This study provides evidence of an association between CD209 and CD209L polymorphisms and TB development in a Brazilian population, suggesting that variations in these genes may influence the protection and susceptibility to infection caused by M. tuberculosis.
Keywords: Adult; Alleles; Brazil; Case-Control Studies; Cell Adhesion Molecules; Dendritic Cells; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Lectins, C-Type; Male; Mycobacterium tuberculosis; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface; Tuberculosis; Young Adult